Implementasi CSR: Pendekatan Tri Hita Karana dalam Moderasi Beragama pada Bank BPD Bali Cabang Mataram - Ni Luh Putu Anom Pancawati (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
In line with the development of business requires business actors to create conducive and competitive business competition related to their finances. Apart from that, to build a company's reputation that is influential in the environmental and social fields which have an impact on the economy of business entities, the company has started to carry out social activities known as Corporate Social Responsibility (CSR). These social activities are carried out on the basis that humans cannot carry out their business activities optimally if they do not pay attention to the balance of the surrounding aspects (triple bottom line), which consists of profit, people, planet. In the teachings of Tri Hita Karana the concept consists of Parahyangan, Palemahan and Pawongan. The three components aim to maintain harmonious relations, including relations between people in the concept of religious moderation. This study aims to determine the implementation of Corporate Social Responsibility (CSR) programs in terms of the concept and approach of Tri Hita Karana in religious moderation and its disclosure at the Mataram branch of Bank BPD Bali. The research method uses a qualitative approach. The results show that the implementation of Corporate Social Responsibility (CSR) in the form of corporate philanthropy, cause related marketing, corporate societal marketing, cause promotions and community volunteering has used the Tri Hita Karana concept and approach and views religious moderation as a must for mutual respect and respect both in the environment economic and social so as to improve business performance.